Kepadatan Populasi dan Distribusi Ukuran Cangkang Kerang Lokan (Rectidens sp.) di Perairan Tanjung Mutiara Danau Singkarak, Sumatera Barat - Dea Rahayu Silviana; Jabang Nurdin; - Izmiarti (Jurnal Biologi Universitas Andalas, 2014)
The study about population density and size distribution of clam (Rectidens sp.) at Tanjung Mutiara Singkarak Lake, West Sumatra has been conducted from June to July 2013. The clams were collected using stratified purposive sampling method. Sampling site was decided into three location based on human activities and three depth strata in each location (<5m, 5-10m and >10-15m). The clams were collected using “dauah” (traditional tool to cath shellfish). There were 43 individu of clams that found at Tanjung Mutiara Singkarak Lake. The highest average population density were found at location III (1.444 ind./m2). The highest average population density were found at strata 3 (1.082 ind./m2). Size distribution of clam showed that at each location and strata have different size. The size of the clam between 24.37-88.54 mm. Medium size clam were the most frequent found in comparison with the small size and large clam. Small clam distributed at strata 2 (5-10 m) locations I and III and strata 3 (> 10-15 m) location III. While large clam only distributed at strata 3 (> 10-15 m) locations II and III. Size distribution of clam varied with the type of substrate and substrate particle.Keywords: clam, Rectidens sp., population density, size distribution